SCHOOL HEALTH PROGRAM BERSAMA SD VITA SCHOOL UNTUK MEWUJUDKAN GENERASI CEMERLANG BEBAS GIGI BERLUBANG - Mohammad Basroni Rizal; Diana Soesilo; Icha Artyas; Noengki Prameswari; Dianty Saptaswari; Cane Lukisari; Budi Handayani; Dwi Andriani; Monika Elidasari; Henu Sumekar; Istien Wardhani; Anindita Apsari; Rizko Wira Artha Megantara (Universitas Hang Tuah Surabaya, 2023)
Introduction. Training of Trainer (ToT) program for teachers and parents for a 21-day morning and evening toothbrush activity teaches children and adults about the benefits of good oral hygiene and shows them how to brush their teeth twice a day with fluoride toothpaste to realizing caries-free Indonesia in 2030 Method. This activity used a digital / online system via the zoom application. Participants' knowledge of dental health was measured through pre-test and post-test questionnaires. Results. The results of the statistical analysis used a paired sample t-test to compare the mean pre-test and post-test scores of the ToT participants showed a significance value (p=0.000). Discussion. There was a significant difference in the level of knowledge of maintaining dental and oral health in teachers and parents of students at Vita School before being given DHE material and after being given DHE through the